The Utilization of a Mixture of Palm Oil and Shellfish Industrial Waste in Producing Paving Block: Producing Paving Block - Aisyah, Siti Aisyah; Imelda, Donna; Busrizal; Hakim, Muhamad Abdul (Jurnal Keteknikan Pertanian, 2024)
Population growth in Indonesia will lead to an increased demand in the development sector. This growth must be balanced by environmentally friendly development practices. Therefore, there is a need for alternative uses of industrial waste for other finished materials. Concrete bricks (Paving blocks) are building construction materials that cover or pave the ground. Boiler ash is one of the solid wastes of the palm oil industry which comes from the remains of burning shells and fibers in boiler machines. Palm oil shells are also one of the solid wastes of the palm oil industry, which comes from the separation between fiber and shells, which occurs in the Light Tenera Dust Separator machine (LTDS). Seashells can be considered solid waste. According to the research findings, paving blocks treated with S1 and S2 exhibit water absorption capacities that comply with the SNI 03-0691-1996 standards, which stipulate a maximum of 8% for C grade, suitable for pedestrian use. Paving blocks treated with S3 also met the SNI 03-0691-1996 standards, with a maximum absorption of 10% for the D grade, which is ideal for covering plants and home gardens. Lower water absorption rates indicate higher quality paving blocks. Variance analysis revealed that the water absorption capacity significantly impacts the quality of the paving blocks. The compressive strength test showed that the paving blocks with S2 treatment had the highest strength, averaging 2,10 MPa. The lowest compressive strength, averaging 1,01 MPa, was observed in the paving blocks treated with S3.